2012
DOI: 10.1038/hdy.2012.59
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and landscape genetics of two endangered frog species of genus Odorrana: different scenarios on two islands

Abstract: Isolation by distance and landscape connectivity are fundamental factors underlying speciation and evolution. To understand how landscapes affect gene flow and shape population structures, island species provide intrinsic study objects. We investigated the effects of landscapes on the population structure of the endangered frog species, Odorrana ishikawae and O. splendida, which each inhabit an island in southwest Japan. This was done by examining population structure, gene flow and demographic history of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 49 publications
3
17
0
Order By: Relevance
“…It is well known that geographic distance is negatively correlated with the dispersal in continuous distributed populations [20][23], but plays variable roles in patchy-distributed populations [24][28]. It is apparent that geographic barriers prevent dispersal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that geographic distance is negatively correlated with the dispersal in continuous distributed populations [20][23], but plays variable roles in patchy-distributed populations [24][28]. It is apparent that geographic barriers prevent dispersal.…”
Section: Discussionmentioning
confidence: 99%
“…The butterfly Maniola jurtina uses a non-random, systematic dispersal strategy and can detect and orient towards habitat from distances of 100–150 m [17]. The genetic and geographic distance between populations are generally positively correlated [20][23], suggesting an isolation-by-distance effect. However, several studies have suggested no correlation existing between geographic and genetic distances [24][28].…”
Section: Introductionmentioning
confidence: 99%
“…While the impacts of activities such as hunting and road mortality may sometimes be directly measurable, Peterman et al (2013) Wood frog (Rana sylvatica) 11 microsats Genetic diversity decreases when approaching the edge of a the species range Igawa et al (2013) Odorrana ishikawae and Odorrana splendida 12 microsats Topography is a key driver of population structure in these species Aguilar et al (2013) Coastal tailed frog (Ascaphus truei) 9 microsats Gene flow is positively correlated with moisture-related variables. Populations do not show signatures of bottlenecks despite heavy logging in the region Richardson (2012) Spotted salamander (Ambystoma maculatum) and wood frog (Rana sylvatica)…”
Section: Amphibian Conservationmentioning
confidence: 99%
“…For example, Hirao and Kudo (2004) reported the genetic structure of snowbed plants along geographic gradients; Bruggeman et al (2010) revealed the effects of habitat fragmentation on genetic variation in the woodpecker population; several researchers (Goldberg and Waits 2010;Murphy et al 2010;Igawa et al 2013;Zancolli et al 2014) also analysed the impacts of habitat heterogeneity on genetic structure of frog population. A common approach used in landscape genetic studies is to compare the matrices between genetic distances and geographic or landscape distance of isolated populations in large scales .…”
Section: Introductionmentioning
confidence: 99%